Profesionalisme Aparatur terhadap Kepuasan Masyarakat dalam Pelayanan di Kantor Kecamatan Manggala Kota Makassar - Syamsir, Muh.; Sahlania, Onno; Rahman, Rahman (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This research aims to determine the level of professionalism of the apparatus on community satisfaction in providing services at the Manggala District Office and the influence of apparatus professionalism on community satisfaction in services at the Manggala District Office. This research uses a quantitative research type. The results of the research hypothesis test show that all the independent variables of professionalism (skill, readiness, and responsibility) have a significant effect on the level of public satisfaction in getting services at the Manggala Subdistrict Office, then the variable that has the most influence is the employee readiness variable, namely the ability of employees to adapt to the method. New ways of working in providing services, including readiness to use completely digital computer technology.